1998
DOI: 10.1097/00007890-199805270-00023
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of Hemolytic-Uremic Syndrome in Renal Transplant Recipients

Abstract: Risk factors for HUS recurrence in renal transplantation could be identified through this meta-analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
1
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 12 publications
0
38
1
3
Order By: Relevance
“…Prior to genetic testing for aHUS, multiple studies showed recurrence of disease in the recipient together with the appearance of de novo aHUS in the donor. [20][21][22][23][24] On this basis, if a living-related donor transplantation is considered, the donor and recipient should have complete molecular testing of CFH, CFI, CD46 and CFB. In the absence of mutations in these genes or if a deletion of CFHR1 and CFHR3 is found, screening should include circulating autoantibodies for CFH and peripheral blood mononuclear cell CD46 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to genetic testing for aHUS, multiple studies showed recurrence of disease in the recipient together with the appearance of de novo aHUS in the donor. [20][21][22][23][24] On this basis, if a living-related donor transplantation is considered, the donor and recipient should have complete molecular testing of CFH, CFI, CD46 and CFB. In the absence of mutations in these genes or if a deletion of CFHR1 and CFHR3 is found, screening should include circulating autoantibodies for CFH and peripheral blood mononuclear cell CD46 expression.…”
Section: Discussionmentioning
confidence: 99%
“…The overall rate of recurrence for HUS was 28% (342). One-year graft survival was 33% compared to 77% in controls (342). Older age of onset of HUS, shorter interval between HUS onset and transplantation, shorter interval between HUS onset and ESRD, the use of living donors and the use of calcineurin inhibitors were all associated with recurrence (342).…”
Section: The Evaluation Of Renal Transplant Candidates: Clinical Pracmentioning
confidence: 97%
“…There was no difference in the rate of recurrence between first or second transplants. In multivariate analysis, age at onset of HUS, interval between HUS and ESRD, use of calcineurin inhibitors, and living-related donors were statistically significant predictors of HUS (342). The risk for graft failure in patients with posttransplant HUS/ thrombotic thrombocytopenic purpura (TTP) was reported to be 5.4 higher than for patients without posttransplant HUS/ TTP (271).…”
Section: The Evaluation Of Renal Transplant Candidates: Clinical Pracmentioning
confidence: 99%
See 2 more Smart Citations